Triterpenoid betulinaldehyde and betulinic acid from the stem bark of Dillenia ochreata (Miq.) Teijsm. & Binn. ex Martelli - Muharni Muharni; Fadhilla Putria Gunanda; Suci Marzulia Rahman; Heni Yohandi; Julinar Julinar (Universitas Jenderal Soedirman, 2026)
Dillenia ochreata is a traditional medicinal plant used to treat scurvy.The pharmacological activity of D. ochreata as a scurvy drug was related to the content of secondary metabolite compounds.The research aimed to isolate and determine the structure of compounds from the stem bark of D. ochreata and assess their antibacterial activity. The extraction used the maceration method with graded polarity (n-hexane and ethyl acetate).The separation and purification using chromatography methods. The structures were determined by spectroscopic analyses using FT-IR and NMR spectroscopy. The compounds were tested for antibacterial activity against Escherichia coli and Staphylococcus aureus using the diffusion method, and the minimum inhibitory concentration (MIC) was determined by the microdilution method. Two compounds, betulinaldehyde (1) and betulinic acid (2), have been isolated. Betulinaldehyde (1) showed weak antibacterial activity against E. coli with a minimum inhibition concentration (MIC) of 120 μg/mL and moderate activity against S. aureus (MIC 15 μg/mL), while betulinic acid (2) showed weak activity against both bacteria (MIC 120 μg/mL). The betulinaldehyde and betulinic acid were first reported from D. ochreata.